Physiological biomarkers of chronic stress: A systematic review - Noushad, Shamoon; Ahmed, Sadaf; Ansari, Basit; Mustafa , Umme-Hani; Saleem, Yusra; Hazrat, Hina (International Journal of Health Sciences, 2021)
Objective: The basic objective of this systematic review was to identify potential biomarkers for chronic stress. Methods: A systematic review of studies linking biomarkers in people with chronic stress was conducted using PRISMA guidelines. The last 40 years’ studies were included in the systematic review with no age restrictions; animal studies were excluded from the study. Electronic databases including PubMed, Embase, and Google Scholar were searched for the study purpose. The studies were searched using the combinations of search terms that comprised chronic stress together with the keywords hypothalamic-pituitary-adrenal axis (HPA axis), autonomic nervous system (ANS), immune system, metabolic biomarkers, cortisol, hair cortisol, salivary cortisol, urinary cortisol, epinephrine, norepinephrine, adrenocorticotropic hormone (ACTH), brain-derived neurotropic factor (BDNF), metabolic biomarkers, antioxidants, glucose, hemoglobin, C-reactive protein (CRP), cytokines, pro-inflammatory cytokines, anti-inflammatory cytokines, and tumor necrosis factor (TNF). Results: A total of 37 studies out of 671 studies met the eligibility criteria and were included in this review. Potential diagnostic biomarkers of chronic stress included cortisol, ACTH, BDNF, catecholamines, glucose, HbA1c, triglycerides, cholesterol, prolactin, oxytocin, dehydroepiandrosterone sulfate (DHEA-S), CRP, and interleukin - 6 and 8. While the others including antioxidants and natural killer (NK) cells require further validation. Taken together, addition, these stress biomarkers have critical prognostic capacities for stress-associated diseases and therapeutic guidance. Conclusion: This systematic review provides an update to the literature by highlighting the role of physiological biomarkers in chronic stress and describing their prognostic and therapeutic values.